KAJIAN KONSTITUSIONAL INDEPENDENSI DAN AKUNTABILITAS MAHKAMAH KONSTITUSI - Malik Malik (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2010)
Kekuasaan kehakiman menjadi salah satu elemen terpenting dalam struktur ketatanegaraan suatu negara. Dalam konsep negara hukum, baik konsep rechtstaat, the rule of law, maupun nomokrasi Islam, kekuasaan kehakiman menjadi pilar penting tentang bagaimana negara hukum bekerja. Asumsinya, jika kinerja kekuasaan kehakiman buruk, maka akan berimplikasi bagi buruknya negara hukum Indonesia.Judicial authority to be one of the most important element in the constitutional structure of a country. In the concept of law, whether the concept rechtstaat, the rule of law, nor nomokrasi Islam, justice becomes an important pillar of how state law works. The assumption was that if the poor performance of the judicial authorities, it will have significant implications for poor countries to Indonesian law.